WATER RESOURCES DEVELOPMENT IN HILLY MICRO CATCHMENT A CASE STUDY - Satapathy, K.K. (Journal of Soil and Water Conservation, 2022)
Nine small watersheds with areas varying from 0.52 to 3.8 were ha. Instrumented in the experimental farm of ICAR located al Barapani (Meghalaya) to study the effect of land use patterns of hillslope runoff-the principal erosive agent. Considering the potentialities of land uses in the hilly region of North East India, the farming systems studied were: live stock based farming system, timber plantations. agroforestry, agriculture on bench terraces, agri-horti-silvipastoral system, horticulture, natural vegetation, shifting cultivation and pine afforestation. Bench terraces, contour trenches, contour builds, half moon terraces were the major soil conservation measures.Surface runoff from the undisturbed hilly watersheds was very small. Large intense rainfall events with high antecedent moisture content in soils generated most of the runoff from the undisturbed and treated watersheds. As expected the watershed treated with shifting cultivation yielded the highest peak runoff while the one left undisturbed with natural vegetation yielded the minimum peak runoff. Mixed land use systems with appropriate soil conservation measures, namely, bench terraces, contour trenches etc. were most effective in checking soil erosion and relating 90-100 per cent of the annual rainfall in situ.The study quantified the major hydrologic parameters of the water harvesting tanks located in the lower reaches of the hill slopes using a water balance approach. The subsurface flow (inter flow) from the upper slopes contributed 85-90 per cent of annual inflow into the tank and the remaining 10-15 per cent came from direct interception of rainfall and collection of surface runoff. The annual inflow into the pond could be predicted from the inter flow model developed the similar watersheds using annual rainfall as input. A graphical solution has been proposed to estimate the availability of water harvesting projects on small hilly watersheds.